2018
DOI: 10.1002/ppul.24024
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a cystic fibrosis transmembrane conductance regulator (CFTR) modulator on high‐dose ibuprofen therapy in pediatric cystic fibrosis patients

Abstract: We suggest a clinically relevant drug-drug interaction exists between ibuprofen and lumacaftor/ivacaftor. Lumacaftor may cause subtherapeutic ibuprofen plasma concentrations due to the induction of CYP enzymes and increased metabolism of ibuprofen. Based on this analysis, we have modified our use of ibuprofen in several patients after evaluation of this drug-drug interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…In addition, a clinically relevant drug–drug interaction between ibuprofen and lumacaftor/ivacaftor has been recently observed in pediatric CF patients. In particular, it has been shown that lumacaftor may cause subtherapeutic ibuprofen plasma concentrations as a consequence of CYP enzyme induction and increased metabolism of the drug [ 28 ]. Thus, further studies are needed to better define the effect of ibuprofen and other nonsteroidal anti-inflammatory drugs on CFTR activity, as well as the potential interactions between these drugs and the novel therapeutic strategies designed to increase either CFTR expression and/or function.…”
Section: Anti-inflammatory Therapy In Cystic Fibrosismentioning
confidence: 99%
“…In addition, a clinically relevant drug–drug interaction between ibuprofen and lumacaftor/ivacaftor has been recently observed in pediatric CF patients. In particular, it has been shown that lumacaftor may cause subtherapeutic ibuprofen plasma concentrations as a consequence of CYP enzyme induction and increased metabolism of the drug [ 28 ]. Thus, further studies are needed to better define the effect of ibuprofen and other nonsteroidal anti-inflammatory drugs on CFTR activity, as well as the potential interactions between these drugs and the novel therapeutic strategies designed to increase either CFTR expression and/or function.…”
Section: Anti-inflammatory Therapy In Cystic Fibrosismentioning
confidence: 99%
“…A single center evaluation of drug‐drug interaction in nine patients showed that while on ivacaftor/lumacaftor, there was a 41.7% relative reduction in peak serum concentration of ibuprofen, with nearly half of the patients having subtherapeutic levels. This raises the question of monitoring levels when starting ibuprofen therapy with ivacaftor/lumacaftor . A study in adults with CF found that all tested positive for cannaboids on urine immunoassay after initiation of lumacaftor/ivacaftor.…”
Section: Cftr Modulatorsmentioning
confidence: 99%
“…This raises the question of monitoring levels when starting ibuprofen therapy with ivacaftor/lumacaftor. 37 A study in adults with CF found that all tested positive for cannaboids on urine immunoassay after initiation of lumacaftor/ivacaftor. Confirmatory gas chromatographymass spectrometry revealed all but one to be a false positive (the true positive admitted to using cannabis at time of testing).…”
Section: Modulator Interactionsmentioning
confidence: 99%
“…The study by Bruch et al describes one center's experience with the potential therapeutic implications of a drug interaction between lumacaftor/ivacaftor and ibuprofen, based on concerns about in vitro data suggesting that lumacaftor acts as a strong inducer of CYP3A4 enzymes, potential inducer of CYP2B6, CYP2C8, CYP2C9, and CYP2C19 enzymes, and inhibitor of CYP2C8 and CYP2C9 enzymes . Given the increasing availability and development of cystic fibrosis transmembrane regulator protein (CFTR) modulators and other therapeutic agents, this study is both timely and important.…”
mentioning
confidence: 99%
“…Stepping down therapy is not currently common practice in CF care—likely because there is also a lack of guidance for CF clinicians on if and when it may be acceptable to step down therapy once a newer agent (eg, CFTR modulator) is added, or when one should replace one therapy for another. For example, we see that, based on the study by Bruch et al that concurrent use of high dose ibuprofen and lumacaftor/ivacaftor is not advised as therapeutic ibuprofen plasma concentrations (and its potential therapeutic benefit) is likely lost. Thus, patients who were previously on high dose ibuprofen and subsequently started on lumacaftor/ivacaftor, should likely be “scaled back” to a regimen including one or the other, not both agents simultaneously.…”
mentioning
confidence: 99%